Liquid Soap from Waste Cooking Oil Containing Betel and Aloe Vera Creates Low Risk to Allergic Contact Dermatitis in Rat Skin - Rahayu, Sri; Huda, Nurul; Priambodo, Rizky; Rusdi, Rusdi; Lisanti, Elsa (Trends in Sciences, 2024)
The quality of used cooking oil can be improved by purifying it using bagasse activated charcoal. Purified used cooking oil can be used as raw material for soap. Use of soap can cause allergic contact dermatitis (ACD). Skin suffering from ACD is characterized by inflammatory cell infiltration of the skin, the inflammatory cells involved are mast cells, macrophages and polymorphonuclear cells (PMN), namely basophils, eosinophils and neutrophils. Therefore, inflammatory cells were chosen as a parameter for the ACD response to the use of used cooking oil liquid soap containing betel and aloe vera. Liquid soap formed was use an extract concentration of 4.5, 9 and 15 %. Skin sensitivity testing was tested on male Wistar rats aged 2 - 3 months for 14 days. Quantitative data was obtained through histopathological examination of the number of inflammatory cells, which were analyzed statistically. The results showed that the use of liquid soap with an extract concentration of 9 % (4.24 ± 0.74) and 15 % (3.96 ± 0.25) had no effect on basophil infiltration. The use of liquid soap with an extract concentration of 4.5 % (2.96 ± 1.17, 6.42 ± 0.86, 5.96 ± 0.38), 9 % (3.12 ± 0.47, 4.62 ± 0.68, 6.42 ± 1.06) and 15 % (3.36 ± 0.41, 5.08 ± 0.30, 6.44 ± 0.55) had no effect on infiltration of neutrophils, eosinophils and macrophages. The use of liquid soap with an extract concentration of 9 % (4.60 ± 0.86) had no effect on mast cell infiltration. Therefore, it can be concluded that the best concentration of 9 % extract betel and aloe vera showed no infiltration of inflammatory cells in rats’ skin given soap from waste cooking oil. Thus, that the soap formed from waste cooking oil treated with bagasse activated charcoal and contain betel and aloe vera is predicted safe to used. HIGHLIGHTS High use of cooking oil results in high waste of cooking oil. Used cooking oil can be used to make liquid soap. Betel and Aloe Vera have antiseptic and anti-inflammatory benefits. The ingredients in soap can cause an Allergic Contact Dermatitis (ACD) response, one of which is characterized by infiltration of inflammatory cells in skin tissue. Polymorphonuclear inflammatory cells (PMN), namely Basophils, Neutrophils, Eosinophils; Mast Cells; and Macrophages are inflammatory cells involved in ACD. The addition of green betel leaf extract and aloe vera did not have a significant effect on inflammatory cell infiltration. Betel and aloe vera extracts have the potential to act as anti-inflammatories in the ACD response. This research shows that used cooking oil liquid soap with an extract concentration of 9 % is the best liquid soap formulation because it does not have a significant effect on the infiltration of PMN inflammatory cells, mast cells and macrophages. GRAPHICAL ABSTRACT